This problem has been solved!

Do you need an answer to a question different from the above? Ask your question!

# Transform the given function (f,x) as described and write the resulting function as an equation g(x). f(x)=√x translate right 1 unit translate down 3 units 1 ƒ(z) = z² reflect across the x-axis translate left 3 units translate up 1 unit :: g(z) = √2+1+3 #g(z)=√2-3+1 #g(x)=-(-3)² +1 #g(z)=(-(2-3))² +2 g (2)=√2-1-3 g(z)=√√2+3+1 g(a). -(z+3)²+1 g(z)-(-(2-2))² +3

**Related Book For**

## Discovering Advanced Algebra An Investigative Approach

1st edition

Authors: Jerald Murdock, Ellen Kamischke, Eric Kamischke

ISBN: 978-1559539845